2015
DOI: 10.1002/qua.24925
|View full text |Cite
|
Sign up to set email alerts
|

Organic fluorines as halogen bond donors: Theoretical study and crystallographic evidence

Abstract: Organic fluorines usually cannot act as halogen bond donors, as a result of the extreme electronegativity and least polarizability of the fluorine atom. However, when the electronegative ability of the substituents bound to the carbon atom is very strong, organic fluorines do show positive electrostatic potentials (ESPs) along the CF bond and thus can form halogen bonds with electron donors. In this work, the effects of six different substituents, i.e., NO2, CF3, CN, COOH, CHO, and CCH, on the ESPs of the F a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Figure shows molecular electrostatic potential (MEP) maps for the XPh molecules. As is usually observed, FPh does not exhibit a σ‐hole, consistent with the general observation that fluorine does not engage in halogen bonds. For ClPh, though the anisotropy of the electron density around the halogen atom is apparent from the MEP plot, the effect of this anisotropy is to produce an approximately neutral region (indicated by the green region) at the extension of the CCl bond.…”
Section: Resultssupporting
confidence: 90%
“…Figure shows molecular electrostatic potential (MEP) maps for the XPh molecules. As is usually observed, FPh does not exhibit a σ‐hole, consistent with the general observation that fluorine does not engage in halogen bonds. For ClPh, though the anisotropy of the electron density around the halogen atom is apparent from the MEP plot, the effect of this anisotropy is to produce an approximately neutral region (indicated by the green region) at the extension of the CCl bond.…”
Section: Resultssupporting
confidence: 90%
“…Since the pioneering work by Brinck et al, many studies have used molecular electrostatic potential maps to demonstrate the σ‐hole in possible halogen‐bond donors, see for example references . Figure shows the electrostatic potential surfaces of the halogenated methyluracil molecules studied in this work.…”
Section: Resultsmentioning
confidence: 99%
“…This has been attributed to the high electronegativity of fluorine and its tendency to engage in significant sp hybridization, which produces an influx of negative charge into the region where the positive σ‐hole would be . Some recent studies state that organic fluorines can form halogen bonds when strongly electronegative substituents are bound to the carbon . However, it has been suggested that this type of bond should not be labelled a halogen bond, as there are fundamental differences between these interactions and halogen bonds involving Cl, Br, and I .…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that intermolecular contacts (Lommerse et al, 1996) between X(Cl, Br, I)Á Á ÁO/N are highly attractive and directional due to the anisotropic distribution of electron density on halogen, whereas FÁ Á ÁO/N does not occur at all; this was claimed based on the CSD study. There are many gas-phase models (Eskandari & Lesani, 2015;Wang et al, 2015;Varadwaj et al, 2015) present in recent literature explaining the presence of a positive electrostatic potential on fluorine leading to halogen bonding, although there are only a few reports which claim fluorine to feature halogen bonding in 'solid-state' geometry. For instance, the presence of a -hole (Clark et al, 2007) on the fluorine atom leads to the presence of a halogen bond in FÁ Á ÁF and FÁ Á ÁS contacts (Pavan et al, 2013); a similar type of result was recently reported showing inter-halogen ClÁ Á ÁF (Hathwar & Row, 2011;Dikundwar & Row, 2012) and homo-halogen FÁ Á ÁF (Hathwar et al, 2014;Hathwar & Row, 2011) interactions.…”
Section: Introductionmentioning
confidence: 99%